Hypoxia signature derived from tumor-associated endothelial cells predict prognosis in gastric cancer - Ruiheng Wang; Ruiheng Wang; Guijun Liu; Guijun Liu; Ke Wang; Zhanglei Pan; Zhanglei Pan; Zhihua Pei; Xijiao Hu; Xijiao Hu (Frontiers in Cell and Developmental Biology)
BackgroundA hypoxic metabolism environment in the tumors is often associated with poor prognostic events such as tumor progression and treatment resistance. In gastric cancer, the mechanism of how hypoxia metabolism affects the tumor microenvironment and immunotherapy efficacy remains to be elucidated.MethodsWe used the bulk-mapping method to analyze the signatures correlated with the response of immunotherapy in the single-cell dataset. Cellular, pathway, and gene were systematically analyzed in both single-cell and bulk validation datasets.ResultsThe most significant cell proportion difference between the response and non-response groups was in endothelial cells, which represent the malignant cells. VWF was specifically overexpressed in endothelial cells and was the hub gene of differential genes. EPAS1 was a VWF trans-regulated gene and highly positively correlated with VWF in expression. Knockdown experiments demonstrated that siVWF reduced the expression of VWF, EPAS1, and HIF1A, as well as the synthesis of lactate and adenosine which are indicators of hypoxic metabolism. These results suggest that the overexpression of core malign endothelial genes such as VWF drives hypoxic metabolism in tumors and creates an immunosuppressive environment that reduces the efficacy of immunotherapy. The adverse prognosis of the hypoxia signature was validated in the bulk cohort and significance was further enhanced after selecting core genes and combined survival weight scoring.ConclusionIn summary, high expression of the malignant endothelial cell driver genes VWF and EPAS1 enhances hypoxic metabolism, and malignant cell-immune cell interactions suppress the immune response. Therefore, the two core genes of hypoxic metabolism might represent potential therapeutic and predicting biomarkers for immunotherapy of gastric cancer in the future.